Preparing for a pandemic: Spending dynamics and panic buying during the COVID-19 first wave - Martin O'Connell; Áureo de Paula; Kate Smith (Institute for Fiscal Studies (IFS), 2020)
We study consumer spending dynamics during the first infection wave of the COVID-19 pandemic using household scanner data covering fast-moving consumer goods in the United Kingdom. We document a large spike in spending for storable products, such as food staples and household supplies, in the days before lockdown. Demand increases were concentrated in 30 of 138 product categories, e.g. soap, soup, canned goods and dried pasta. Households in all socioeconomic groups exhibit unusually high demand pre-lockdown, but there is a clear gradient, with the largest demand spikes for wealthier households. Although stories of people purchasing extreme amounts received a lot of attention, higher aggregate demand was mainly driven by more households than usual choosing to buy storable products, with only small increases in average quantities bought on a given trip. Temporary limits on the number of units per transaction, introduced following the demand spike, are therefore unlikely to lead to the avoidance of stock-outs. Given rapidly increasing case numbers in the ongoing second wave, and the spectre of further national lockdowns, our work provides timely evidence for preparing for a future demand spike.
Keywords: D12; D18; I30; 330; panic buying; hoarding; coronavirus